Understanding Social Learning Processes in a Citrus Farming Community of Practice - Linda Downsborough (Environmental Association of Southern Africa, 2009)
his paper focuses on what would traditionally be termed 'non-formal' learning processes in the context of a case study examining how citrus farming communities in the Patensie Valley in the Eastern Cape in South Africa were learning conservation practices. Communities of Practice theory was used to provide a conceptual framework for researching these learning interactions. Through historical and other qualitative research methods, I was able to establish that farmers in this community of practice learned mainly through responding to change and uncertainty, through forming and drawing on networks and community structures, through intergenerational learning, and through various interactions with each other. The historical research also pointed to the significance of policy and market-based changes in farmer learning, and their attachment to the land, which is shaped through historical associations with the land, and through embedded relations in farming practice cultures. The paper provides an example of how Communities of Practice theory, complemented by historical research, can be used to understand non-formal learning.